Multiscale imaging of plant development by light-sheet fluorescence microscopy - Ovečka, Miroslav; von Wangenheim, Daniel; Tomančák, Pavel; Šamajová, Olga; Komis, George; Šamaj, Jozef (Nature plants, 2018)
Light-sheet fluorescence microscopy (LSFM) methods collectively represent the major breakthrough in developmental bio-imaging of living multicellular organisms. They are becoming a mainstream approach through the development of both commercial and custom-made LSFM platforms that are adjusted to diverse biological applications. Based on high-speed acquisition rates under conditions of low light exposure and minimal photo-damage of the biological sample, these methods provide ideal means for long-term and in-depth data acquisition during organ imaging at single-cell resolution. The introduction of LSFM methods into biology extended our understanding of pattern formation and developmental progress of multicellular organisms from embryogenesis to adult body. Moreover, LSFM imaging allowed the dynamic visualization of biological processes under almost natural conditions. Here, we review the most important, recent biological applications of LSFM methods in developmental studies of established and emerging plant model species, together with up-to-date methods of data editing and evaluation for modelling of complex biological processes. Recent applications in animal models push LSFM into the forefront of current bio-imaging approaches. Since LSFM is now the single most effective method for fast imaging of multicellular organisms, allowing quantitative analyses of their long-term development, its broader use in plant developmental biology will likely bring new insights.
Keywords: Plant Development; Microscopy, Confocal; zemědělské plodiny; Crops, Agricultural; Animals; Models, Biological; Microscopy, Fluorescence; vývoj rostlin; biologické modely; Arabidopsis; zvířata; konfokální mikroskopie; fluorescenční mikroskopie